THE ATTRACTIVENESS OF LOCAL LABOUR MARKETS AND THE DIVERSITY OF DEVELOPMENT LEVELS - THE CASE OF WEST POMERANIA REGION - Chądzyńska, Elżbieta Julia (Acta Universitatis Lodziensis. Folia Oeconomica, 2015)
Modern research methods of economic development of regions and cities pay special attention to the position of the units in the area expressed by geographical position, the distance between the tested individuals and neighbourhood, especially near places with significant economic potential.Modeling of spatial mobility of residents through the use of methods based on identifying the forces affecting positively and negatively on the movement of people in an organized space let us to find places attractive to a large number of citizens.The article presents the use of intervening opportunities model in order to generate a distribution of travel to work and to determine the diversity of individual attractiveness due to the offer of jobs and position in transportation network. Modeling was made for the set of cities. Because situation in cities should be compared with situation in their environment occurrence of spatial relationships and clusters in gminas of West Pomerania region was detected by using Moran’s I statistic. The analysis covers the area of West Pomerania and its surrounding. This is a specific area where the differentiation of the level of development is particularly dependent on the position in geographical space.